Strategy And Implementation of Students’ Character Education Implementation in State 9 Sila Primary School - Atmaja, Jessy Parmawati; RS, Yuyun Yuningsih (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This This study aimed to describe: (1) the implementation of character education strategy in schools; and (2) the implementation of character education at SD Negeri 9 Sila. This research was a qualitative descriptive study. The data collection was done by observation, interview,and documentation. Data validity was checked by triangulation techniques, by comparing the information from the results of interviews with documentation and observation. The results showed that the strategy of implementation of character education at SD Negeri 9 Sila was conducted through: integrating values and ethics in the school subjects, the internalization of positive values instilled by all of the school community members, habit formation and training, giving an example and role model, the creation of an atmosphere of a school with character in, and habit formation. The implementation of character education at SD Negeri 9 Sila was done through the interestedness of character formation with teaching and learning, school management, and extracurricular activities.